A Review on Deep Learning in Robotics - Shimi, PS; Shajan, PX (International Journal of Computer Sciences and Engineering, 2025)
During the last few decades, there has been a rush in research in the area of deep learning. In this paper we have made a review on the limitations of deep learning in physical robotic systems, using currently available examples. It is mainly focused on the recent advances made in robotics community and application of deep learning in robotics